Kinerja Pramusaji Berdasarkan Gender - Suci Sandi Wachyuni (Media Wisata, 2020)
The issue of gender equality in tourism is again a hot topic. Men still dominate jobs in the world of tourism, especially in the food and beverage sector. In general, women are synonymous with gentle and emotional characteristics, while men are considered firm and rational. So that there are still many food and beverage sectors that prefer male workers to female workers. Work in restaurants is required to carry heavy loads and is dominated by other physical work. This study aims to analyze differences in employee performance based on gender. Researchers take a case study at the Amuz Gourmet Jakarta Restaurant. The research method used is a mixed-method. The quantitative analysis method used was ANOVA and triangulation of qualitative data